Use of laparoscopic videos amongst surgical trainees in the United Kingdom. Issue 6 (December 2019) - Celentano, Valerio; Smart, Neil; Cahill, Ronan A.; McGrath, John S.; Gupta, Sharmila; Griffith, John P.; Acheson, Austin G.; Cecil, Tom D.; Coleman, Mark G.
Abstract: Background: Surgical trainers consider laparoscopic videos as a useful teaching aid to maximize trainees' learning and skill development given the backdrop of time constraints and productivity demands. Aim of this study is to assess the current use of laparoscopic videos amongst surgical trainees in the United Kingdom. Methods: A steering committee of 15 experienced laparoscopic trainers from 8 countries developed a survey on the use of laparoscopic videos by surgical trainees. The survey items were finalized by discussion through e-mails, teleconferences, and face-to-face meetings and a finalised questionnaire was distributed amongst surgical trainees in the United Kingdom. Results: 92 trainees were invited and 75 returned the questionnaire (81.5%). 86.7% of the trainees routinely watched online surgical videos and the more frequently used websites were Youtube.com and Websurg.com. Trainees require laparoscopic videos to have supplementary educational content such as English commentary (90.7%) and use of snapshots (93.3%) and diagrams (86.7%). Position of the patient and trocars, indication for surgery, preoperative data and postoperative outcomes are required characteristics of laparoscopic videos. 29 trainees (38.7%) do not record the laparoscopic procedures they perform, despite the majority of them recognising the usefulness of routine video-recording for training purposes (78.7%). Conclusions: Surgical trainees consider videos a useful adjunct in laparoscopic surgery training, with preference for open access sources. Trainees value highly informative videos with supplementary educational content.